2015
DOI: 10.5380/acd.v16i2.41145
|View full text |Cite
|
Sign up to set email alerts
|

1,2,4-oxadiazole: A Brief Review from the Literature About the Synthesis and Pharmacological Applications

Abstract: Este trabalho contempla uma breve revisão da literatura, empregando os periódicos das bases de dados Scielo, Sciencedirect e ACS, sobre os métodos mais utilizados para síntese do anel 1,2,4-oxadiazólico, destacando suas vantagens e desvantagens. Foi realizada também uma pesquisa sobre as principais funções deste grupamento, sua ação no tratamento de doenças, os testes realizados para a confirmação das ações farmacológicas e os resultados obtidos.Palavras-chave: oxadiazolas; síntese; farmacologia. ABSTRACT:This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Importantly, the heterocycle demonstrates bioisosteric equivalence with ester and amide moieties due to the possibility of creation specific interaction (e.g., hydrogen bonding). It is a particularly useful alternative when the instability of those groups is observed (e.g., when the hydrolysis may appear) [20,21]. Nowadays, there are a few commercially available drugs containing 1,2,4-oxadiazole nucleus such as Oxolamine, Prenoxdiazine (cough suppressant, Figure 3) Butalamine (vasodilator, Figure 3), Fasiplon (nonbenzodiazepine anxiolytic drug, Figure 3), Pleconaril (antiviral drug, Figure 3), Ataluren (Duchenne muscular dystrophy treatment drug, Figure 3) and Proxazole (a drug used for functional gastrointestinal disorders, Figure 3) [22][23][24].…”
Section: Historical Remarks-124-oxadiazolementioning
confidence: 99%
“…Importantly, the heterocycle demonstrates bioisosteric equivalence with ester and amide moieties due to the possibility of creation specific interaction (e.g., hydrogen bonding). It is a particularly useful alternative when the instability of those groups is observed (e.g., when the hydrolysis may appear) [20,21]. Nowadays, there are a few commercially available drugs containing 1,2,4-oxadiazole nucleus such as Oxolamine, Prenoxdiazine (cough suppressant, Figure 3) Butalamine (vasodilator, Figure 3), Fasiplon (nonbenzodiazepine anxiolytic drug, Figure 3), Pleconaril (antiviral drug, Figure 3), Ataluren (Duchenne muscular dystrophy treatment drug, Figure 3) and Proxazole (a drug used for functional gastrointestinal disorders, Figure 3) [22][23][24].…”
Section: Historical Remarks-124-oxadiazolementioning
confidence: 99%
“…50 It is a particularly helpful alternative when ester or amide group instability is noted (for example, when hydrolysis may manifest). 51,52 Several molecules with a wide range of biological activities, including anticancer, anti-inflammatory, anticonvulsant, antiviral, antibacterial, antifungal, antiangiogenic, and analgesic properties, have been identified through extensive exploration of the 1,2,4-oxadiazole heterocycle. 53 It was demonstrated that the 1,2,4-oxadiazole scaffold exhibited inhibitory potency against various receptors such as kappa opioid receptor (KOR), 54 human deacetylase sirtuin 2 (HDSirt2), 55 carbonic anhydrase (CA), 56 histone deacetylase (HDAC), 57 and cyclooxygenase-2 (COX-2).…”
Section: Introductionmentioning
confidence: 99%
“…When the instability of these moieties (such as hydrolysis) is discovered, 1,2,4‐oxadiazole is a highly effective alternative. [ 14,15 ] Fasiplon (a nonbenzodiazepine anxiolytic drug), prenoxdiazine (a cough suppressant), butalamine (a vasodilator), ataluren (a treatment drug for Duchenne muscular dystrophy), proxazole (a drug used for functional gastrointestinal disorders), pleconaril (an antiviral drug), and doxylamine are some of the commercially available drugs that contain the 1,2,4‐oxadiazole nucleus (Figure 2). [ 16–18 ]…”
Section: Introductionmentioning
confidence: 99%